Major sources of mercury emissions to the atmosphere: The U.S. case. (15th February 2019) - (Thanos) Bourtsalas, A.C.; Themelis, Nickolas J.
Highlights: The 2014 total anthropogenic emissions of mercury in the U.S. were 51.4 tons. The largest source of anthropogenic mercury were coal-fired pilot plants. Mercury in municipal solid wastes decreased by a factor of four. Since 2001 the U.S. WTE industry mercury emissions were reduced by a factor of seven. The APC systems of the WTE plants had an average efficiency of 96.3%. Abstract: In 1989, the two major sources of mercury emissions to the atmosphere in the U.S. were coal-fired power plants (80 tons Hg) and waste to energy power plants (82 tons Hg). This paper examines what has happened to these two major sources of mercury emissions since 1989. A comparison within the waste management industry is, also, provided. The 2014 total anthropogenic emissions of mercury in the U.S. were 51.8 t. The results of the analysis of emissions by industrial sector showed that the largest source of anthropogenic mercury were coal-fired power plants. Among industrial processes, the ferrous metals recycling and the cement industries were the largest emitters of mercury. With regard to waste-to-energy power plants, all of which, since the nineties, have installed advanced emission control systems, the results have been very satisfactory: The authors obtained mercury emission data from operators of most of the waste-to-energy (WTE) power plants in the US. The results showed that in 2014 the 77 U.S. WTE plants in total emitted 0.4 tons of mercury, corresponding to 0.77% of the U.S. total. This number was one half of that reported by the National Emissions Inventory (NEI) for "municipal waste combustion'' (0.64 t) due to the fact that the NEI survey included incinerators without energy recovery. A 2002 Earth Engineering Center study had shown that the mercury emissions of the U.S. WTE industry decreased from 81.8 t in 1989 to 2.2 t in 2001. The present study showed that between 2001 and 2014 the U.S. WTE industry mercury emissions were reduced further, by a factor of seven.